1995
DOI: 10.1074/jbc.270.51.30813
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies of Human Recombinant 74- and 54-kDa L-Histidine Decarboxylases

Abstract: We have expressed and characterized human recombinant 74-kDa (rHDC74) and 54-kDa (rHDC54) L-histidine decarboxylases (HDCs) in Sf9 cells. By immunoblot analysis, rHDC74 and rHDC54 were shown to be localized predominantly in the particulate and soluble fractions, respectively. rHDC74 exhibited histamine-synthesizing activity equivalent to that of rHDC54. The existence of 74-and 54-kDa HDCs was also confirmed in the particulate and supernatant fractions of the cell lysate, respectively, from the human basophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 25 publications
0
31
1
Order By: Relevance
“…Although we previously showed that in vitro cleavage by elastase of the 74-kDa form, which exhibited a low enzyme activity, resulted in generation of an active 53-kDa form (16), it remains to be clarified whether enzymatical activation occurs upon post-translational processing of HDC in histamine-forming cells. In expression systems, mouse and rat 74-kDa form of HDC were found to exhibit no or little enzyme activity, although enzyme activity of human 74-kDa form was reported to be equivalent to that of the 54-kDa C-terminal deletion mutant (15,18,32). Our results strongly indicate that the proteolytic conversion itself plays a critical role in enzymatic activation of HDC, at least in the mouse mastocytoma cell line.…”
Section: Discussionmentioning
confidence: 61%
“…Although we previously showed that in vitro cleavage by elastase of the 74-kDa form, which exhibited a low enzyme activity, resulted in generation of an active 53-kDa form (16), it remains to be clarified whether enzymatical activation occurs upon post-translational processing of HDC in histamine-forming cells. In expression systems, mouse and rat 74-kDa form of HDC were found to exhibit no or little enzyme activity, although enzyme activity of human 74-kDa form was reported to be equivalent to that of the 54-kDa C-terminal deletion mutant (15,18,32). Our results strongly indicate that the proteolytic conversion itself plays a critical role in enzymatic activation of HDC, at least in the mouse mastocytoma cell line.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, the primary translation product generated by the pEP-HDC1.5 vector lacks a total of 170 amino acids from the carboxy terminus of the primary HDC sequence. This construct is similar in design and size to constructs which have been used in previous studies (8,47,48), where it was assumed that HDC cleavage involves only carboxy-terminal processing. It was predicted to generate a primary translation product of 54 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recombinant experiments showed that a 54-kDa carboxy-terminally truncated HDC isoform had much greater activity than the primary translation product, leading to the general belief that such a regulated step in vivo would facilitate the production of an enzymatically active homodimer of 100 to 110 kDa (8,42,46,47). However, other groups were unable to confirm that the 54-kDa isoform had a higher specific activity (48), and the presence of other isoforms has to some extent been ignored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in the molecular mass was explained by post-translational processing that truncates a C-terminal region of ϳ20 kDa. The C-terminal truncated 54-kDa form of human recombinant HDC possessed sufficient catalytic activity to support histamine synthesis (15). Therefore, the C-terminal truncated HDC is considered as an active form.…”
mentioning
confidence: 99%